THE CONVERSATION: Feedback Structures, Ways of Knowing, and Neurodivergence. (1st June 2019) - Holt, Allison Leigh
This paper discusses communication as a community of feedback systems. Arguing that meaningful communication between human and non-human species is contingent upon first reconsidering human understandings of human consciousness and cognition, the author identifies axes of communication as perceiving-sensing, adjusting-processing, and responding-exchanging, beyond language. Drawing upon theories of enactivism and her work teaching media to neurodivergent students, the author proposes experimental time-based media as a useful model for communication between humans and the not-quite-fixed world of all things that exist, with or without categorization, and between those things themselves.